Spurious hyperfixation of hexamethylpropyleneamine oxime in acute embolic stroke. - Shintani, S; Tsuruoka, S; Satoh, Y (American Journal of Neuroradiology, 1995)
A 71-year-old man with atrial fibrillation suddenly had an embolism in the right middle cerebral artery. Single-photon emission CT was performed 4 hours after the onset of stroke and revealed markedly elevated 99mTc-hexamethylpropyleneamine oxime (HMPAO) uptake in the right frontotemporoparietal region. This area of HMPAO hyperfixation corresponded to the area of infarction, as determined by CT and MR. Our findings showed that HMPAO single-photon emission CT overestimated reflow hyperemia after reperfusion in the acute stage of embolic stroke, as it does in the subacute stage.